Pengolahan Pati Rumbia menjadi Serbuk Glukosa secara Hidrolisis Enzimatis dengan Variasi Perbandingan Pati dan Air, Suhu Evaporasi, dan Suhu Pengeringan - Dewi, Erwana; Yerizam, Muhammad; Az’zahrah, Nandyta Rizqi (Talenta Publisher (Universitas Sumatera Utara), 2024)
Glucose is a simple sugar that can be used as an sucrose alternative. Rumbia starch is rich in carbohydrates and abundant in Indonesia, potentially being used as a raw material for the production of glucose powder. The process involves starch hydrolysis, evaporation, and drying. The purpose of this study was to obtain optimal conditions of reducing sugar content, evaporation, and drying temperature based on variations in starch and water ratio (1:3, 1:4, 1:5, and 1:6), evaporation temperature (100 °C and 115 °C), and drying temperature (50 °C, and 70 °C). From this study, the optimal ratio of starch and water was 1:4 with a reduced sugar content of 99,77%. The optimal evaporation temperature was 115 °C, the brix content obtained is 85%, and the optimal drying temperature was 70°C, the water content obtained is 3,60%. Based on SNI of glucose, the glucose powder products meet the standard for water content and ash content. However, only in the ratio of starch and water 1:4 and 1:5, the reducing sugar content met the SNI of glucose.